2017
DOI: 10.1038/s41598-017-08963-2
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface binding, uptaking and anticancer activity of L-K6, a lysine/leucine-rich peptide, on human breast cancer MCF-7 cells

Abstract: Cell surface binding and internalization are critical for the specific targeting and biofunctions of some cationic antimicrobial peptides (CAPs) with anticancer activities. However, the detailed cellular process for CAPs interacting with cancer cells and the exact molecular basis for their anticancer effects are still far from being fully understood. In the present study, we examined the cell surface binding, uptaking and anti-cancer activity of L-K6, a lysine/leucine-rich CAP, in human MCF-7 breast cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 40 publications
5
53
0
Order By: Relevance
“…The detected intracellular fluorescence intensity of EGFP‐CAT was 3‐6 times that of EGFP‐LL37, EGFP‐IL, EGFP‐L‐K6, and EGFP‐TAT (Figure D). This result indicates that the cell‐penetrating ability of CAT is significantly higher than that of other reported AMP‐derived CPPs, even higher than the classical CPP TAT. Therefore, we have identified a novel AMP‐derived CPP with high penetration efficiency from the buCATHL4 family.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…The detected intracellular fluorescence intensity of EGFP‐CAT was 3‐6 times that of EGFP‐LL37, EGFP‐IL, EGFP‐L‐K6, and EGFP‐TAT (Figure D). This result indicates that the cell‐penetrating ability of CAT is significantly higher than that of other reported AMP‐derived CPPs, even higher than the classical CPP TAT. Therefore, we have identified a novel AMP‐derived CPP with high penetration efficiency from the buCATHL4 family.…”
Section: Resultsmentioning
confidence: 77%
“…Similarly, IL is a 13 amino acid bovine‐derived AMP that has been shown to significantly promote the gene transfer of polycationic vectors . Another AMP‐derived CPP is L‐K6, a natural cationic AMP isolated from the skin secretions of the Chinese brown frog ( Rana chensinensis ), which could be internalized into MCF‐7 cells mainly through clathrin‐independent macropinocytosis without significant cell surface disruption . Furthermore, it has been reported that some AMPs can selectively penetrate tumor cells, for example, buforin IIb, which is a cell‐penetrating AMP that showed selective cytotoxicity against tumor cells .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that the anticancer activity of peptides can cause DNA damage. Internalization of L‐K6 (lysine/leucine‐rich peptide) induced dramatic nuclear damage and MCF‐7 breast carcinoma cell death without significant cytoskeleton disruption . Other peptides, such as gaegurin 6 and PTP7, have anticancer activity against human cancer cells without cytotoxicity against peripheral blood mononuclear cells and minimal hemolytic activity .…”
Section: Discussionmentioning
confidence: 99%